Kunst aus Frankfurt. (Frankfurt : Degussa AG, 1989)
Blum, Heiner ; Bury, Claus ; Domenig, Gerald ; Falk, Petra ; Fischer, Bernd ; Goepfert, Hermann ; Hörl, Ottmar ; Laurer, Istvan ; Mattner, Jakob ; Mon, Franz ; Peschick, Irene ; Raab, Joachim ; Rögler, Michael ; Schewior, Sigrid ; etc.
boek